ULTRASOUND EXAMINATION CRITERIA FOR THE CHOICE OF SURGICAL TREATMENT IN PATIENTS WITH OBLITERATING ATHEROSCLEROSIS OF THE LOWER EXTREMITIES - Horlenko, F. V. (Проблеми клінічної педіатрії, 2019)
Introduction. Critical ischemia of the lower extremities is a major indication for primary reconstructive surgery, since only restoration of the main blood flow can preserve the limb and improve the quality of life of patients [1, 3]. But in 17 - 70% of patients with critical ischemia, due to the lesion of the distal vascular bed, there are no conditions for performing reconstructive operations, which causes a high frequency of primary limb amputation - up to 25 - 90% [6, 9]. Purpose. To study and analyze ultrasound duplex scan data of the lower extremity arteries in order to select the optimal method for deep femoral artery reconstruction. Materials and methods. The results of a comprehensive examination and surgical treatment of 182 patients who were operated at the vascular surgery department of the Zakarpattya Regional Clinical Hospital named after Andriy Novak were studied and analyzed (from 2000 to 2017), regarding critical ischemia based on the obliterating atherosclerosis of the lower extremities vessels. Results. Based on the data obtained by ultrasound duplex scan of the lower extremity arteries, the main diagnostic criteria of the pathology were identified. The indications for the implementation of various methods of profundoplasty were determined. Conclusions. Ultrasound duplex scan of the lower extremity arteries is the optimal non-invasive method for determining the indications for various methods of profundoplasty. The main ultrasound criteria include the degree, extent of stenosis, plaque density, and deep-popliteal index, which allow us to select patients for profundoplasty and to choose the optimal method for reconstruction of the deep femoral artery.